PROSPEK DAN PROBLEMATIKA PELAKSANAAN APEC - Awani Irewati (Jurnal Penelitian Politik, 2010)
This essay attempts to analyseproblems andprospects ofthe APEC existence in dealing with the organizationsprinciples implementation Afew years ago the Asia Pack Economic Cooperation APEC one ofthe most meaningful organization in the region has been criticizedfor conducting insufficient efforts in addressing the 1997Asiacrisis Nowadays the organization is currentlyfacing the internal detrimental challenges ofthe raising FTA basedeconomic cooperations i e ASEAN China FTA ASEAN Japan FTA even bilateral based FTAs within the AsiaPacific region These FTAs could turn APEC out to be either breakable or even stronger It is hoped that thepowerfulFTA basis should be a cornerstone towards the sturdy APEC The paper comes to the conclusion that the APECwhich meets the two region Asia and Pacific is an convincinglyfeasible organization to remain taking the yearlydialogue between the developed and developing members This is truly becoming a lucrative opportunity for themembers to express what they want to getfrom this organization